2007
DOI: 10.1063/1.2759880
|View full text |Cite
|
Sign up to set email alerts
|

Vortex ring head-on collision with a heated vertical plate

Abstract: International audienceWe report experimental results of the normal impact of a vortex ring in air on a vertical heated plate at constant temperature. We address the case in which the natural convection boundary layer is laminar and the vortex ring is stable. Vortex rings are created by pushing air through a circular exit orifice of a cavity, using a piston-cylinder system. The impinging vortex ring perturbs both the thermal and dynamical boundary layers where we measure the total heat flux exchanged by the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…Many tests were performed where only thermal data were recorded and it was found that these high levels of localized heat transfer were consistently present and always at least double the free convection level. This is in stark contrast to the value of 15 % reported from spatially averaged measurements (Arévalo et al 2007) and illustrates that the vortex has a very localized but dominant impact on the convection.…”
Section: Vortex-ring-wall Interaction and Resulting Heat Transfercontrasting
confidence: 54%
See 1 more Smart Citation
“…Many tests were performed where only thermal data were recorded and it was found that these high levels of localized heat transfer were consistently present and always at least double the free convection level. This is in stark contrast to the value of 15 % reported from spatially averaged measurements (Arévalo et al 2007) and illustrates that the vortex has a very localized but dominant impact on the convection.…”
Section: Vortex-ring-wall Interaction and Resulting Heat Transfercontrasting
confidence: 54%
“…Vortex rings have been extensively investigated and are very well understood from a fluid mechanics standpoint (Shariff & Leonard 1992) but not much work is available considering vortex-ring flows in combination with heat transfer. In a recent experimental investigation (Arévalo et al 2007) a vortex ring was created in air and allowed to impact on a heated vertical plate. The spatially averaged heat transfer from the surface was found to increase by up to 15 % over natural convection levels while the vortex was in contact with the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different experimental works have studied the collision of single vortex rings with vertical heated walls. [10][11][12] Arévalo et al 10 studied the interaction of a vortex ring in air in collision with a vertical heated wall, their results indicated that there was an increment of the heat transfer as a result of the impact which increases with the vortex Reynolds number. Later, Arévalo et al 11 expanded their study and conducted measurements with the particle image velocimetry (PIV) technique to show that the vorticity and shear stresses are the basic ingredients to enhance the heat transfer.…”
Section: Introductionmentioning
confidence: 97%
“…Different wall temperatures, Reynolds numbers, and piston stroke ratios are considered. Previous works [10][11][12] have shown that the interaction of the vortex ring and the thermal boundary layer generates an asymmetric expansion of the ring. We will show that this asymmetry is also observed in the trajectory of the vortex ring during collision.…”
Section: Introductionmentioning
confidence: 99%
“…1 The mechanism has revealed particular features that make the vortex ring a realistic candidate to enhance heat transfer from small electronic devices. A simplified situation involving this collision mechanism has been reported by other authors providing important insight on vortex stretching [2][3][4] and pressure gradients 4,5 at the wall, where the vortex core could be responsible for local and peaked shear stresses.…”
Section: Introductionmentioning
confidence: 99%